A solution to RPCs of satellite imagery with variant integration time. Issue 351 (1st November 2016) - Cao, B.; Qiu, Z.; Zhu, S.; Meng, W.; Mo, D.; Cao, F.
Abstract : To get a sufficient swath width and the higher resolution, most spaceborne cameras acquire the ground information by multiple time delay integration charge-coupled devices. Owing to the special imaging mechanism, TDI charge-coupled devices (CCD) is required to adjust the integration time dynamically. If the offset between two adjacent chips in the along-track direction is large enough, integration time adjustment will generate innegligible pixel offsets in different integration segments. Under this circumstance, if the PRCs are solved by traditional terrain-independent strategy, which uses the rigorous sensor model to generate evenly distributed object-image points, system errors are inevitably introduced and thus the rational polynomial coefficients (RPCs) cannot obtain the high fitting accuracy. In this paper, we derived the quantitative relationship between integration time and pixel offsets. The RPCs fitting technology based on integration time equalisation for improving the fitting accuracy was then discussed. The potential for this method to yield high fitting accuracy and the ability to keep raw object-image relations are illustrated with the experimental results obtained with four high-resolution imageries of Mapping Satellite-1 (TH-1).